South Korean best practice, applied to Malaysian ship-repair and shipbuilding (SRSB) industry - Ahmad Murad, Omar, Dato' Ir. (The Institution of Engineers, Malaysia (IEM), 2016)
Link to publisher’s homepage at http://www.myiem.org